Counterinsurgency Doctrine Applied to Infectious Disease - Kirkup,Benjamin C (PeerJ PrePrints, 2014)
Recent scientific discoveries lead inexorably to the conclusion that the ‘total human’ incorporates a necessary body of numerous microbes, including bacteria. These bacteria play a very important role in immunity by actively resisting infections by outside bacteria; however, under certain conditions they can degrade their community. They can arrogate to themselves resources that normally flow through other metabolic pathways and form persistent biological structures. In this situation, these bacteria constitute an insurgency, with strategic ramifications.
Keywords: counterinsurgency; infectious disease; microbiome; microbiology; microbial ecology; insurgency; war metaphor; antibiotics; antivirulence; pathogen